SEPASARAN PEDHET: Respon Masyarakat Kalangundo Grobogan Jawa Tengah Terhadap Qs. Al-Baqarah: 261 - Sujoko, Ahmad; Mustofa, Ahmad; Abidin, Zaenal (Wahana Islamika: Jurnal Studi Keislaman, 2023)
The sepasar tradition in parts of Java is an event to announce the name of the newborn to the guests. However, in Grobogan, sepasar events are not only held for the birth of a baby but also for the birth of a pedhet (calf). This qualitative research, which was designed using the living Qur'an study model, aims to find out the religious meaning of the Grobogan people for the pedhet sepasaran ritual through a reception approach to QS. Al-Baqarah: 44. This study concludes that the people of Kalangundo Grobogan understand that the ritual of sepasar pedhet is nothing but an expression of alms and prayer (zikr) together to ask for safety for newly born the calf so that they become intermediaries for obtaining the blessings of fortune from Allah SWT.